About the Artist - Ring, Sinead (feminists@law, 2013)
The cover artist for this issue is Hannah Tiernan, who <span style="color: black; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;">is c<span style="background: white; color: #333333; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;">urrently studying art at the National College of Art and Design, Dublin. She works mainly in sculpture, installation and photography. The photograph <span style="background: white; color: #333333; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;">is part of an installation piece consisting of a large scale mono print on calico. In front hangs a muslin sheet imprinted with footprints and reflecting a projected series of fallen angles. For further information on the project, click on the attached document. More of Hannah Tiernan's work is on show at: https://www.facebook.com/HannahTiernanArtist?ref=stream.